(untitled) (CIPEEX, 2022)
SUPBRAIN IS AN EDUCATIONAL ASSISTANCE PLATFORM FOR PEOPLE WITH NEURODIVERGENTS, SUCH AS ADHD AND AUTISM. THIS SOFTWARE IS BEING DEVELOPED THROUGH LEAN INCEPTION AND SCRUM DAILY METHODOLOGIES, IN SEARCH OF BRINGING MORE ACCESSIBILITY TO THESE PEOPLE, BRINGING MORE ENGAGEMENT TO THE SCHOOL ENVIRONMENT AND A DYNAMIC THAT WORKS FOR THESE USERS. AS A RESULT, WE CURRENTLY HAVE A NAVIGABLE PROTOTYPE MADE IN FIGMA, BUT WILL STILL UNDERGO MODIFICATIONS DUE TO THE INITIAL STATE OF THE PROJECT, BUT WE CAN SEE SOME OF OUR FEATURES ALREADY IN IT. WE EXPECT TO HELP A LOT OF PEOPLE WITH THIS PROJECT, SOME OPPOTURNITIES APPEREAD TO US WHICH CAN FACILITATE OUR PATH IN THIS JOURNEY.&NBSP;